STUDY OF THE BACTERIAL ACTIVITY OF SILVER NANOPARTICLES (AGNPS) PRODUCED USING CYNOPHYTA ALGA EXTRACT (SPIRULINA PLATENSIS). - Dhuha Raheem Azooz Abbood1, Zainab Abd Ameer Mohammed2 (Chelonian Research Foundation, 2024)
The study included the production of biologically produced silver nanoparticles (AgNPs) by the algae extract Spirulina platensis, as well as the diagnosis of some effective chemical compounds from the blue-green algae S.platensis and the evaluation of the inhibitory effectiveness of silver nanoparticles (AgNPs) against some types of pathogenic bacteria that included Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus. Different concentrations of silver nanoparticles (0.5, 1, 1.5 and 2) mg/ml were prepared to study their effect on the types of bacteria studied by determining the area of ​​diameter of bacterial growth inhibition. The silver nanoparticles showed their microbial effectiveness against two isolates of Gram-negative bacteria, E.coli and P.aeruginosa and the isolate of Gram-positive bacteria S.aureus, where the average diameter of the inhibition zone for the concentrations used was 12.58, 13.75 and 15.24 mm, respectively, by the diffusion well method. Bio-synthesized silver nanoparticles from the algae extract S. platensis, at very low concentrations, proved effective against the bacterial species studied. The results of drug susceptibility testing using the disk method showed that all bacterial isolates were 75% resistant to the antibiotics Amoxicillin, Chloramphenicol, Ciprofloxacin, Clindamycin, Trimethoprim/Sulfamethoxazole and Tetracyclin, while 25% were sensitive to the antibiotics Imipenem and Piperacllin/Tazobactam. The results of the drug susceptibility test using the Vitec system also showed that the E.coli bacteria were resistant to the antibiotics Ampicillin, Piperacillin/Tazobactam, Cefazolin, Cefoxitin, Ceftazidime, Ceftriaxone, Cefepime, Imipenem, Ciprofloxacin, Levofloxacin, Trimethoprim/Sulfamethoxazole at a rate of 73.3% , As for the antibiotics Amikacin, Gentamicin, Tigecycline and Nitrofurantoin, the sensitivity rate was 26.7%. As for the P. aeruginosa bacteria, it was 100% resistant to all antibiotics used. The S.aureus bacteria resisted the antibiotics Benzylpenicillin, Oxacillin, Ciprofloxacin, Erythromycin, Clindamycin, Tetracycline, Fusidic Acid and Rifampicin by 57.1%, while the antibiotics to which it was sensitive included Moxifloxacin, Linezolid, Teicoplanin and Trimethoprim/Sulfamethoxazole by 42%. 9%.